Peningkatan Efikasi Diri Matematika melalui Metode Belajar Mind Map - Gita Aulia Nurani; Asmadi Alsa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to test empirically the effect of the mind maps visual learning method on increasing the self-efficacy of learning mathematics in junior high school students. The research design used a quasi-experimental design with the one-group pretest-posttest design. The research subjects were collected using a non-random purposive sampling technique with 22 students who had moderate to low self-efficacy scores. Data collection used the mathematics self-efficacy scale, and data analysis using repeated analysis of variance. The results showed that there was a difference in the average score of learning mathematics self-efficacy between pre-test and post-test. This finding may indicate that the mind maps visual learning method has a positive effect on increasing the self-efficacy of learning mathematics in junior high school students. The increase in the average self-efficacy score in the generalization dimension was 5.8 points, the level dimension was 4.5 points, and the strength dimension was 3.1 points.